Elderly Gymnastics Reduces Blood Pressure in Hypertensive Elderly - Najihah, Najihah; Ramli, Rahmawati (Window of Health : Jurnal Kesehatan, 2018)
Elderly tend to experience health problems caused by decreased body function due to aging process. The most common health disorder experienced by elderly is the decline of the cardiovascular system. Heart valve thickens and becomes stiff, the heart's ability to pump blood decreases by 1% per year, decreased cardiac output, decreased heart rate to stress response, loss of elasticity of blood vessels, increased blood pressure due to peripheral vascular resistance. This study aims to determine the effect of elderly gymnastics on changes in blood pressure in the elderly in the work area of ​​Rappokalling Health Center. The research design used was pre-experiment with one group pre-test-post test, with the number of samples counted 14 people. Sampling in this research is non probability sampling. Intervention given that elderly gymnastics performed for 3 weeks with a frequency of 3 times a week duration 15-30 minutes. Data were tested with Paired Sample T-test. The results of this study indicate a significant difference in elderly gymnastics treatment to changes in systolic blood pressure (p value 0.02) and diastolic blood pressure (p value 0,000) in elderly hypertension in the work area of ​​Rappokalling Health Center so it can be concluded there is influence of elderly exercise decrease in blood pressure in elderly hypertension and it is expected that elderly gymnastic exercises can routinely be non-pharmacological therapy in the provision of nursing care in elderly patients.